The Tongue-Tied Imagination : Decolonizing Literary Modernity in Senegal - Warner, Tobias (Book collections on Project MUSE., 2019)
Should a writer work in a former colonial language or in a vernacular? The language question was one of the great intractable problems that haunted postcolonial literatures in the twentieth century. But instead of asking whether language matters, The Tongue-Tied Imagination explores how the language question itself came to matter--Provided by publisher.